(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
The research team had conducted this work at a private orchard in Saqlawiya – Falluja district in 2019 to investigate the influence of foliar application of liquorice (glycyrrhizin) extract (GLE) and humic acid (HA) on some vegetative growth traits and yield of Al-Ibrahimi apple cultivar. The factorial experiment consisted of 2 factors; the first one was GLE which consisted of 3 levels (L0, L1, L2) of (0, 3, and 6 g.L-1) respectively; while the second one was HA with 4 levels (0, 2, 4, and 6 g.L-1) had symbols of (H0, H1, H2, and H3) successively. Thus, the total number of treatments was 12 of 3 replications. Every apple tree considered as an experimental unit. The HA treatments were applied 7 times to soil every 20 days starting from 20th February 2019 while the foliar applications of GLE were 5 times starting from the 1st April in the same year. A significant improvement in vegetative growth, quantity, and quality of yield due to GLE and HA applications has been shown in increasing individual leaf area (LA), length of branches (LOB), number of leaves (NOL), total chlorophyll content in leaves (TCL) , and total carbohydrates content in leaves (TCCL), average weight of fruits (AWF), and number of fruits per tree (NFT) that reflected positively on increasing yield per individual tree (YPT), total percentage of soluble solids (PSS), vitamin C content in fruits (CC) , and decreasing acidity of fruits (TPA). The interaction between factors had significant influence in most of studied traits. Thus the L1H3, L2H2, and L2H3 treatment had the best results.